Modular Pressure and Flow Rate-Balanced Microfluidic Serial Dilution Networks for Miniaturised Point-of-Care Diagnostic Platforms - Nikolaos Vasilakis; Konstantinos I. Papadimitriou; Hywel Morgan; Themistoklis Prodromakis (Sensors, 2019)
Fast, efficient and more importantly accurate serial dilution is a necessary requirement for most biochemical microfluidic-based quantitative diagnostic applications. Over the last two decades, a multitude of microfluidic devices has been proposed, each one demonstrating either a different type of dilution technique or complex system architecture based on various flow source and valving combinations. In this work, a novel serial dilution network architecture is demonstrated, implemented on two entirely different substrates for validation and performance characterisation. The single layer, stepwise serial diluter comprises an optimised microfluidic network, where identical dilution ratios per stage are ensured, either by applying equal pressure or equal flow rates at both inlets. The advantages of this serial diluter are twofold: Firstly, it is structured as a modular unit cell, simplifying the required fluid driving mechanism to a single source for both sample and buffer solution. Thus, this unit cell can be used as a fundamental microfluidic building block, forming multistage serial dilution cascades, once combined appropriately with itself or other similar unit cells. Secondly, the serial diluter can tolerate the inevitable flow source fluctuations, ensuring constant dilution ratios without the need to employ damping mechanisms, making it ideal for Point of Care (PoC) platforms. Proof-of-concept experiments with glucose have demonstrated good agreement between simulations and measurements, highlighting the validity of our serial diluter.